The needs for medical visit accompaniment services among older patients with chronic diseases and their family members: a qualitative study - Yu-Han Chen; Jia-Ying Zhu; Qin-Ying Fu; Xin-Ye Yu; Chang-Hong Wu; De-Qin Huang (Frontiers in Public Health)
ObjectiveTo explore the specific needs of older patients with chronic diseases and their family members for medical visit accompaniment services in outpatient settings.MethodsThe interview outline was developed based on the theory of existence, relatedness, and growth needs. Semi-structured in-depth interviews were conducted with older patients and their family members. Directed content analysis was used to analyze the interview data. This study followed the Consolidated Criteria for Reporting Qualitative Research (COREQ) guidelines to report the study.ResultsNineteen older patients with chronic diseases and 17 family members, were interviewed in the outpatient clinic of a tertiary hospital in Hangzhou from July to August 2024. Four themes emerged with ten sub-themes: (1) existence needs (basic services, security, and the qualifications of medical visit accompaniment providers), (2) relatedness needs (relationships with medical visit accompaniment providers and emotional support), (3) growth needs (willingness to learn and learning contents), and (4) the need for optimizing service provision (improving the efficiency of medical visits, ensuring transparency of the visit, and delivering personalized services).ConclusionThe needs of older patients with chronic diseases for medical visit accompaniment services included existence needs, relationship needs, growth needs, and the need for optimizing service provision. The government and institutions providing medical visit accompaniment services should conduct qualification assessment, enhance personnel management, and improve the services as to effectively promote the medical experience and healthy ageing of older patients.